A Large-Area and Nanoscale Graphene Oxide Diaphragm-Based Extrinsic Fiber-Optic Fabry–Perot Acoustic Sensor Applied for Partial Discharge Detection in Air - Wang, Shuchao (Nanomaterials (Basel), 2020)
This article presents an extrinsic fiber-optic acoustic sensor applied for partial discharge (PD) detection in air. A Fabry–Perot (F-P) cavity consisting of a single-mode fiber (SMF) and a graphene oxide (GO) film, whose thickness and effective vibration diameter are approximately 500 nm and 4.377 mm, respectively, is used as this sensing core, and the manufacturing process of GO diaphragms and this sensing probe is illustrated to be simple and controllable. Performance tests indicate that this proposed sensor maintains a linear acoustic-pressure response and a flat frequency response in the range of 200 Hz to 20 kHz, while being an omnidirectional sensor and having high working stability during a ten-day test period. Additionally, PD detection results show that the minimum PD size detected by this proposed sensor in air was approximately 100 pC, which demonstrates that this proposed sensor can achieve high-sensitivity PD detection in air.